Evaluación de riesgos ergonómicos en los puestos de trabajo de la Dirección de Obras Públicas del Gobierno Autónomo Descentralizado Municipal Francisco de Orellana - Sánchez Guamán, Javier Gonzalo (2022)
The present investigation was born from the problem that GADMFO registers, on the progressive development of osteomuscular problems in the workers. In the field research, through surveys and interviews, the existence of ergonomic risk factors was identified and the information was recorded in a check-list of the activities carried out by the staff of the Dirección de Obras Públicas. Using methods of ergonomic risk assessment, RULA (forced postures) and GINSHT (manual handling of loads); It was obtained as a result that the scores obtained from the RULA method for the jobs: workers, mechanics, electrical linemen and welder indicate a level of action 3 and 4, that is, they require redesign and urgent changes in the task; on the other hand, the office staff presents a performance level 2 that indicates that changes may be required in the task. Meanwhile, the result of the GINSHT method in the manual handling of loads by workers presents a non-tolerable risk that can be solved by applying the corrective measures described in the task. In the end, an ergonomic risk prevention manual is proposed to solve the lack of ergonomic knowledge, strengthen safe posture habits and mitigate the development of musculoskeletal disorders at work, through safe work procedures